Indonesian two-week fieldwork in Australia: Great or no impact? - Dewi, Anita Sartika (Journal of English and Education (JEE), 2008)
This paper is a sociolinguistic study on the impact of a two-week fieldwork experienced by English Diploma Program students of Universitas Islam Indonesia(UII)Yogyakarta in Australia. The aspects to be scrutinized are the effect of the program on the students' self development and their understanding of Australia and how their return to Indonesia influences their fellow students at the Islamic university.  Impact of the two-week field work is seen from two theoretical backgrounds language perception (Lowe, 2000) and orientation (Gardner, 1985). Data collection was carried out through email questionnaires. Several themes occurred were expectation on the fieldwork, expectation on life in Australia, family expectation, reality faced in Australia, most meaningful experiences, and returning to Indonesia.Results of the study show that the fieldwork has brought an "instrumentally oriented" impact on the students' self development and understanding of Australia. Even though the students gained more than previously expected, more could have been achieved as there was no strong influence on other UII students, yet.